PERAN PEMERINTAH DAERAH DALAM PENCEGAHAN PENCEMARAN AIR SUNGAI AKIBAT LIMBAH PABRIK DI KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - Egi Putra; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study describes the role of the local government in this case the Environmental Service in river water pollution preventing due to factory waste in Pancung Soal District, Pesisir Selatan Regency. The Environment Agency carries out control, supervision and restoration to prevent river water pollution due to factory waste with various activities in every aspect. This research uses descriptive qualitative method. Informants were selected using a proportional sampling technique. Test the validity of the data using the observation persistence technique. The data was collected by means of interviews, observation and document analysis studies. The data analysis technique is done by means of data reduction, data presentation and drawing conclusions. The results of this study indicate the role of the Department of the Environment in preventing river water pollution has been carried out well and optimally even though there are many obstacles and problems in the field